Literary fairy-tale as a subject of philosophical analysis: structuralist and post-structuralist dimensions - НoncharenkoKateryna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2019)
Quite often study of fairy-story forms in the context of philosophy is estimated as a whimsical urge of an intellectual/philosopher who seeks to establish fairness and balance in the distribution of research attention between all spheres of human existence. It is worth recognizing that such statements especially in the context of our today are banal and even meaningless. A tale that is the concentration of the plurality of hidden functions could be considered a symptom or recipe from grave “diseases contemporary”. While the symptom of a form of fairy-stories shows all the transformations and changes of the present-day priorities, the recipe appears to be an invitation to the world of magic plots that compel to understand the cruel reality. The article analyzes the structure of fairy-stories basing on consideration of the works of theorists of structuralism and post-structuralism who highlight the issues of philosophical substantiation of fairy-stories form and its place in humanitarian sciences. The problems of folk and literary tales, as well as authorship and sense of fairy tales are considered